Speaking as anxiety in ielts examinations : a case study in the perspective of Bangladeshi examinees - Ahmed, Md. Kawser (Penerbit Universiti Kebangsaan Malaysia, 2021)
Speaking is a good form of anxiety among IELTS examinees around the world. Examinees well efficient in speaking often fail to claim a good score in this particular kind of band. They think of it as a big hurdle to speak before an examiner, create own story for conversation and make understand the examiner what message and information he possesses. This scenario happens to both native and non-native speakers, though non-natives go through a great struggle in the way of speaking. The purpose of this paper is to highlight IELTS speaking as a form anxiety and stressful matter. IELTS candidates find speaking session non-interactive but a way of demonstration which leads the candidates towards obstacles in getting good score. In fact, speaking in IELTS examinations requires some specific techniques in which examinees can make a positive impression upon examiner’s minds overcoming all kinds of psychological barriers like stress, and anxiety and confusion in the way of speaking. This paper will focus on the anxieties in terms of IELTS speaking, scenario of speaking performance in IELTS and lack of speaking performance and possible remedies from psychological backdrops. In addition, this paper will concentrate on the conduction of research work in the context of Bangladeshi examinees where IELTS examination has become popular for many academic and professional or vocational reasons.